Fiscal Reform in Costa Rica: Price Elasticities of Major Food Categories to Inform Decision-Making - Dal, Eléonore; Rivera, Rodrigo; Morales Opazo, Cristian; Madrigal, Mariela (Frontiers in Nutrition, 2022)
In the context of fiscal reform in Costa Rica (value added tax revision), the definition of a new basic tax basket, “canasta básica tributaria” (CBT) in Spanish, incorporating nutritional criteria is underway in the country. In this study, price elasticities of major food categories were analyzed using a Quadratic Almost Ideal Demand System (QUAIDS) model. Data from the 2018 National Survey of Household Income and Expenditures was used. Measuring price elasticities is essential because it allows: knowing the extent to which food demand reacts to price changes, anticipating changes in the quantities demanded as a result of fiscal policy changes, measuring potential substitution and complementary effects between food groups, and potential nutritional effects of fiscal policies. As a result, it helps providing recommendations on the content of a CBT with nutritional criteria. Results show that the food categories with the most elastic demand are “Bread and cereals,” soft drinks and “Milk, cheese and eggs.” Substitution effects exist between the following groups: “Fruits” and “Oils and fats,” “Fruits” and “Bread and cereals,” and between “Milk, cheese and eggs” and “Oils and fats.” For this last food category and for the one which includes sweets and chocolates, the consumption decreases when the price of “Bread and cereals” increases. They are complementary goods. These relations between food groups need to be taken into account when defining a national CBT with nutritional criteria and with the objective of promoting the consumption of healthier food groups while disincentivizing the consumption of the unhealthy ones. Lastly, it is important that the consumption of the healthiest foods within each food group be fiscally promoted. Clinical Trial Registration JEL codes: D12, H3, I18.